Heterogeneity and Dynamics of Vasculature in the Endocrine System During Aging and Disease - Stucker, Sina; De Angelis, Jessica; Kusumbe, Anjali P. (Frontiers in Physiology, 2021)
The endocrine system consists of several highly vascularised glands that produce and secrete hormones to maintain body homeostasis and regulate a range of functions and processes, including growth, metabolism and development. The vasculature functions as the main transport system for hormones and provide regulatory signals for endocrine cells and therefore is essential for proper endocrine function. The specialized vasculature within the endocrine tissues creates a nurturing microenvironment for stem and progenitor cells, thereby critical for their survival, maintenance and differentiation. Moreover, the vasculature interacts with endocrine cells, supporting their endocrine function. However, the structure and niche function of endocrine gland vasculature remains incompletely understood. Aging and endocrine disorders are associated with vascular perturbations. Understanding the cellular and molecular cues driving the disease, and age-related vascular perturbations hold potential to manage or even treat endocrine disorders and comorbidities associated with aging. This review aims to describe the structure and niche functions of the vasculature in various endocrine glands and define the vascular changes in aging and endocrine disorders.